A brief history of cyberspace - Ning, Huansheng ([Place of publication not identified] : Auerbach Publications, 2022)
With the widespread growth of the Internet, a new space - cyberspace - has appeared and has rapidly been integrated into every facet of life and work. It has effectively become the fourth basic living space for human beings. Although cyberspace has become a topic of increasing widespread concern, it is still difficult to understand cyberspace well because of its many definitions, vast and varied content, and differences with other similar spaces. A Brief History of Cyberspace attempts to establish a complete knowledge system about the evolution and history of cyberspace and cyber-enabled spaces (i.e., cyber-enabled physical space, cyber-enabled social space, and cyber-enabled thinking space). By providing a comprehensive overview, this book aims to help readers understand the history of cyberspace and lays a solid foundation for researchers and learners who are interested in cyberspace. The book has three main objectives: To provide a comprehensive understanding of the development of cyberspace, ranging from its origin, evolutions, and research status to open issues and future challenges, as well as related hot topics in industry and academia. To examine cyber life, cyber syndrome, and health in addition to cyber-enabled spaces designed for better living. To describe cyberspace governance from the perspective of the individual, society, and national and international levels in order to promote a more profound and reasonable direction to the development of cyberspace. Consisting of 16 chapters, the book is divided into three parts. Chapter 1 introduces the origins and basic concept of cyberspace, cyber philosophy, and cyber logic to help readers have a general understanding of cyberspace. Chapters 2 through 7 discuss a wide variety of topics related to human behavior, psychology, and health to help people better adapt to cyberspace. Chapters 8 through 16 present the history of cyberspace governance and various social and culture aspects of cyberspace. Each chapter concludes with a discussion of future development.
1. Cyberspace, Cyber Philosophy, and Cyber Logic2. Cyberspace Behavior Development and Research History3. History of Online Social Network4. Research History on Cyber-Enabled Disease (Cyber Syndrome)5. Cyborg: A Fusion System of Human and Electronic Machinery6. The Brief History Research of Digital Twin7. Psychology and Emotion Research History in Cyberspace8. The History of Gender Research in Cyberspace9. Taking a Glimpse through the Future of Cyberethics10. Cyber-Religion: Past, Present, and Future11. Cyberspace Culture and Art Research History12. Cyberspace Sovereignty Development and Research History13. Cyberspace Governance Coordination Mechanism14. Cybercrime and Research History15. A Brief History of Cyberspace Legislations16. A Brief History of Cyber War
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Internet / General; COMPUTERS / Internet / World Wide Web; COMPUTERS / Virtual Reality; Internet -- History; Cyberspace -- History